Implementasi Ajaran Tat Twam Asi Terhadap Mahasiswa Penyandang Tunanetra Di IHDN Denpasar - I Gusti Lanang Arya Wesi Kusuma (Jayapangus Press, 2019)
The teachings of Hinduism have three basic frameworks, namely tattwa (philosophy), susila (ethics) and events (ritual). The moral aspect is very important in social life because humans cannot live alone. The teaching of morality teaches the ethics of behaving as a living human being with various differences to realize a harmonious relationship with fellow human beings. This is done by the Institut Hindu Dharma Negeri Denpasar (IHDN) Institute as one of the open universities willing to accept blind students. All students, both normal and needy are considered equally entitled to get the highest education. This is an implementation of the teachings of Tat Twam Asi in Hinduism. This study uses theories such as: Functional Structural Theory used to dissect the problem in the form of the implementation of the Tat Twam Asi teachings for blind students in IHDN Denpasar. Symbolic Interaction Theory used to dissect the problem of obstacles in the implementation of the Tat Twam Asi teachings on blind students in IHDN Denpasar. Behaviorism Theory is used to dissect the problem of the impact of the implementation of the Tat Twam Asi teachings on blind students in IHDN Denpasar. To get accurate data used qualitative research methods with data collection techniques used are observation, interviews, documentation and literature study. This research found the form of implementation of Tat Twam Asi teachings on blind students in Denpasar IHDN in the form of Tri Kaya Parisudha behavior and the practice of Paramita Chess. Two forms of implementation of the Tat Twam Asi teachings have become the function of IHDN Denpasar as one of the Hindu state universities in preparing Hindu human resources who are not only superior in Dharma, Widya, and Culture, but also able to apply the principles of tolerance needed in group life orcommunity. Obstacles in the implementation of Tat Twam Asi's teachings on students with visual implementasion in IHDN Denpasar consist of external barriers in the form of adjustments to the new environment, and internal barriers in the form of limitations in seeing and mentally blind students who are not confident so they become inferior. Obstacles or obstacles can be resolved through mutual understanding among the people by implementing the Tat Twam Asi teachings to overcome any obstacles. Language or symbols used to resolve obstacles must be clear in interacting. The impact of the implementation of the Tat Twam Asi teachings for students with visual impairments in IHDN Denpasar is three, namely the social impact of the formation of kinship and harmonious relations; the impact of religion with increasing religious emotion in the form of gratitude; and the ethical impact of manners, compassion, respect, and openness accept differences.